(Re)fashioning Philippine street foods and vending. Issue 1 (28th August 2019) - Milgram, B. Lynne
Abstract : A hallmark of many Global South city streets is ambulant vendors' daily trade in prepared and fresh foods. Yet governments often restrict such informal and sometimes illegal enterprises, privileging instead privatized and sanitized streetscapes—policies that disrupt urbanites' livelihoods and their consumption options. Engaging these issues, this article analyzes how street food vendors in Baguio, northern Philippines, mitigate the constraints of government street vending bans to establish viable and alternative food provisioning enterprises. I explore how vendors' location‐responsive political, social, and economic practices interweave with new street market design and consumption patterns to yield a distinctive taste of place while underpinning livelihood sustainability. Exercising "street politics, " some banned vendors joined the established Harrison Road Night Market, while others collectively established distinctive storefront eateries. That city officials enabled the legitimacy of formerly illegal and informal street vendors by incorporating their enterprises into these registered commercial venues evidences officials' complicity in formalizing informality when this policy is to their advantage. I suggest that through their politics‐on‐the‐edge, Baguio's relocated street food vendors emerge as effective visible actors in public arenas that have largely excluded their voices in where, and the conditions within which, they work.